Peptic Ulcer Diseases in Patients with Liver Cirrhosis and Portal Hypertension: Experience in a Tertiary Level Hospital in Bangladesh - Moben, Ahmed Lutful; Kafee, Md Abdullahel; Kabir, Md Jahangir; Raha, Arunanagshu; Majid, Farjana; Razzak, Md Abdur (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Cirrhosis of liver and peptic ulcer disease (PUD) are very common in Bangladesh. PUD may coexist with cirrhosis and portal hypertension. Haematemesis and melaena in cirrhosis of liver are not always from ruptured oesophageal varices; rather it may be due to bleeding peptic ulcer disease. Objective: To find the prevalence of PUD among patients with liver cirrhosis and portal hypertension. Materials and Methods: This cross sectional, descriptive study was conducted on 96 patients of cirrhosis of liver diagnosed with oesophageal varices at endoscopy unit of Kurmitola general hospital, during endoscopic evaluations in 4 months period from september 2017 to december 2017. Results: Total cirrhotic patients enrolled were 96 (M=61, F=35), mean age was 51.8 ± 14.2 yrs (18-86years). Hepatitis B virus (HBV) was the leading cause of cirrhosis in 54.1%, Hepatitis C virus (HCV) 5.2 %, proven non-alcoholic steatohepatitis (NASH) were 11.5% and rest were from unknown aetiology. Their average Child-Turcotte-Pugh (CTP) score were 8.6 (12-5), 37.6% associated with portal hypertensive gastropathy. Grade-III oesophageal varices found in 52 patients, whereas grade-II in 25 patients. Among this 96 patients 39 (40.6%) revealed peptic ulcer disease more in the form of gastric ulcer (n=23) than duodenal ulcer (n=10) and both (n=6). Most of the ulcers belonged to Forrest class III (76.9%). Conclusions: Variceal bleeding and portal hypertensive gastropathy are the common causes of bleeding and anaemia in patients with cirrhosis of liver. Peptic ulcer disease has been found to be one of the potential causes of haematemesis, melaena, and anaemia among these patients in Bangladesh. Large multicenter controlled studies are needed to confirm the reports. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 68-71